2022
DOI: 10.1128/aac.01431-21
|View full text |Cite
|
Sign up to set email alerts
|

Loss of GdpP Function in Staphylococcus aureus Leads to β-Lactam Tolerance and Enhanced Evolution of β-Lactam Resistance

Abstract: Infections caused by Staphylococcus aureus are a leading cause of mortality. Treating infections caused by S. aureus is difficult due to resistance against most traditional antibiotics, including β-lactams. We previously reported the presence of mutations in gdpP among S. aureus strains that were obtained by serial passaging in β-lactam drugs. Similar mutations have recently been reported in natural S. a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 33 publications
3
27
0
Order By: Relevance
“…Recent studies have demonstrated that CDA plays important roles in regulating vital biological processes such as DNA repair, ion homeostasis, and central carbon metabolism among others (2)(3)(4)(5). In addition, CDA has also been implicated in controlling processes that are important for bacterial pathogenesis such as biofilm formation, antibiotic tolerance, and virulence (6)(7)(8)(9)(10). CDA mediates its function through binding to its cognate effectors (i.e.…”
Section: Main Textmentioning
confidence: 99%
See 4 more Smart Citations
“…Recent studies have demonstrated that CDA plays important roles in regulating vital biological processes such as DNA repair, ion homeostasis, and central carbon metabolism among others (2)(3)(4)(5). In addition, CDA has also been implicated in controlling processes that are important for bacterial pathogenesis such as biofilm formation, antibiotic tolerance, and virulence (6)(7)(8)(9)(10). CDA mediates its function through binding to its cognate effectors (i.e.…”
Section: Main Textmentioning
confidence: 99%
“…Recent studies have highlighted that increased CDA concentrations promote tolerance to β-lactam antibiotics and allow cell wall restructuring (8,11). Furthermore, a growing number of contemporary clinical surveillance studies have identified mutations in gdpP among β-lactam resistant or non-susceptible natural isolates of S. aureus (12)(13)(14)(15).…”
Section: Main Textmentioning
confidence: 99%
See 3 more Smart Citations